Unleashing customer empathy in the circular economy: Development of a high-calcium fish sausage prototype from fermented fish residue - Sasichakorn Wongsaichia; Phaninee Naruetharadhol; Teerapong Pienwisetkaew; Somsamorn Gawborisut; Chavis Ketkaew (Future Foods, 2024)
In a circular economy, fermented fish residue could be converted into high-calcium fish bone powder for fish sausages to reduce fish waste. To create product concepts for such sausages, this study aimed to (1) identify customer behaviors, needs, and problems associated with purchasing fish sausages; (2) select high-value consumers of high-calcium fish sausages from fermented fish residues; and (3) propose product prototypes of high-calcium fish from fermented fish residues. We interviewed 50 sausage purchasers and a particular producer of calcium fish bone powder. Then, thematic analyses were performed to evaluate the minimum viable product (MVP) for the final high calcium fish sausage prototype. The research suggested that household consumers were the target market for this novel food. This result emphasized nutrition and sensory characteristics as the primary reason for purchasing sausages and indicated common problems with the inaccessibility of healthy sausages. Based on the findings, fish sausage should contain nutritional value and healthy ingredients to address the consumers’ pain points. This circular food system was estimated to make the food product more sustainable and resource-efficient when fully applied.